ANALISIS PERBANDINGAN STRATEGI MARKETING EVENT LINK-UP DAN EVENT PITCH-HUB 2024 OLEH PERUSAHAAN CV VRITIMES - Angelina Azzahra; Heri Setyawan; Djuni Akbar; Etty Kongrat (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2026)
In response to evolving market dynamics and rising competition, companies are increasingly turning to event-based marketing to strengthen audience engagement and brand visibility. This study presents a comparative analysis of the marketing strategies used in two events Link-Up and Pitch-Hub organized by CV VRITIMES. The research aims to evaluate the application of the 4Ps marketing mix (Product, Price, Place, Promotion) and assess each event's effectiveness in meeting strategic goals. Using qualitative descriptive analysis, data were collected through observation, interviews, and documentation. The results indicate that both events successfully utilized digital promotion and targeted professional audiences, though they differed in content design, promotional execution, and budget allocation. These insights contribute to refining future event strategies and offer valuable references for MICE industry practitioners aiming to optimize event marketing performance.